Reproductive biology and feeding habits of the Nile tilapia Oreochromis niloticus (Linnaeus, 1758) (Pisces, Cichlidae) in Lake Hawassa, Ethiopia - Teshome Belay; Elias Dadebo; Girma Tilahun; Degsera Aemro (Fisheries and Aquatic Sciences, 2025)
The study conducted from February 2023 to January 2024 aimed to investigate the reproductive biology and feeding habits of Nile tilapia Oreochromis niloticus in Lake Hawassa, Ethiopia. 816 mixed sexes of O. niloticus were considered for reproductive biology, sampling involved gillnets with mesh sizes of 6, 8, 10, and 12 cm and random samples from landing sites. To get different size ranges additional data were collected for feeding habits and morphometric relationships using smaller sizes of gillnets (2 and 2.5 cm), hand nets (6 mm size), and randomly from local fishers gathered with hooks, resulting in a total sample of 987 collectively. Microsoft Excel, SPSSv27, and MATLAB software were used for data analysis. The results showed that the sex ratio (1:0.93) did not showed deviate from the theoretical 1:1 ratio (χ2, p > 0.05). The TL50% maturity was 18.5 cm for males and 19.1 cm for females. O. niloticus from Lake Hawassa showed year-round breeding with peaking in January and February. Fecundity ranged from 105 to 1,541 eggs/ripe fish. Phytoplankton was the most frequent (95.72%), contributed (88.2%), and preponed (96.6%) in the stomach of O. niloticus. Ontogenetic dietary shifts were not statistically significant (C > 0.6). Significant dietary variations were noted between rainy and dry months, particularly for the occurrence of macrophytes (χ2, p < 0.05) and volumetric contributions of detritus (t-test, p < 0.05). O. niloticus from Lake Hawassa showed positive allometric growth (b >3) and was significantly different from 3 (t-test, p < 0.001). The mean relative condition factors showed significant variation by sampling month (ANOVA, p < 0.05). The result concluded that O. niloticus from Lake Hawassa is categorized as a phytoplanktivorous trophic category. Based on the present findings, it is recommended to stop the harvesting of O. niloticus below 19.1 cm and enforce fishing closures during peak breeding months (January and February). The insignificant dietary shift and phytoplankton dominance in the diet of O. niloticus suggest that a parallel study on phytoplankton biomass and primary production, as a proxy of yield and management of O. niloticus stock in Lake Hawassa, should be considered for future studies.